Amaliyah and Struggle: Comparation of Interpretations of Muhammadiyah Sumbar and LDII Sumbar Towards Jihad Verses and Hadith - Hafizzullah Hafizzullah; Mhd. Alfahjri Sukri; Safriwaldi Safriwaldi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to describe the construction of religious institutions in West Sumatra, especially Muhammadiyah and the Indonesian Islamic Da'wah Council (LDII) West Sumatra regarding the meaning of jihad, as well as to explain the attitude of these religious institutions towards acts of terror in the name of jihad. Qualitative methods were used in this study with data obtained through interviews, documentation, and literature studies, both from books, scientific articles, books, and news. Social construction theory of Peter L Berger to explain the construction of Muhammadiyah and LDII West Sumatra religious institutions about the meaning of jihad. The results showed that Muhammadiyah West Sumatra interpreted jihad in the form of Jihad Amaliyah. The concept of jihad was revealed in various forms of movement, namely Muhammadiyah as an Islamic Movement, Muhammadiyah as the Amar Ma'ruf Nahi Munkar Islamic Da'wah Movement, Muhammadiyah as the Tajdid Movement. The understanding of jihad is then internalized into various forms of programs ranging from da'wah, education, health, social services and humanity. The LDII defines jihad in the sense of struggle. This understanding of jihad can be seen in the internalization of the five West Sumatra LDII cluster programs. Both institutions both reject the meaning of jihad in the sense of war in the Indonesian context. The jihad that is carried out is moderate.